CIPROFLOXACIN OTIC DROPS FOR PREVENTION OF OTORRHOEA FOLLOWING MYRINGOTOMY AND VENTILATION TUBE INSERTION AMONG CHILDREN - Ammar A Selman; Ahmed A Alansary; Abdulwahab B Abdulwahab (Basrah Journal of Surgery, 2017)
CIPROFLOXACIN OTIC DROPS FOR PREVENTION OF OTORRHOEA FOLLOWING MYRINGOTOMY AND VENTILATION TUBE INSERTION AMONG CHILDREN